Effect of the Thickness of a Diamond-Like Carbon Layer on the Local Temperature Increase in a Multilayered Structure Induced by Laser Heating - Yu, Peng; Zhou, Weidong; Yu, Shengkai (Numerical heat transfer. Part A, Applications, 2015)
The present study concerns the effect of the thickness of the overcoating layer on the local temperature increase in the multilayered structure subject to laser heating. The numerical simulation indicates that the presence of the diamond-like carbon (DLC) layer on the top of multilayered structure enhances local temperature increase, compared with the same structure without the DLC layer. This enhancement gradually becomes significant with an increase in the thickness of DLC layer. The DLC layer only absorbs small amount of laser energy. However, the energy accumulates in the DLC layer due to its low thermal conductivity, resulting in significant temperature increase.